Self‐Assembly: Enhanced Self‐Assembly of Metal Oxides and Metal‐Organic Frameworks from Precursors with Magnetohydrodynamically Induced Long‐Lived Collective Spin States (Adv. Mater. 30/2014). (August 2014) - Breynaert, Eric; Emmerich, Jens; Mustafa, Danilo; Bajpe, Sneha R.; Altantzis, Thomas; Van Havenbergh, Kristof; Taulelle, Francis; Bals, Sara; Van Tendeloo, Gustaaf; Kirschhock, Christine E. A.; Martens, Johan A.
<x xml:space="preserve">Abstract</x> The simple combination of a weak magnetic field with turbulent flow during material synthesis results in significantly improved crystalline order and morphology, obtained by mounting a permanent magnet on a tube system. This newly discovered magneto‐hydrodynamic effect is demonstrated by C. E. A. Kirschhock, E. Breynaert and co‐workers on page 5173 for three technologically relevant materials: COK‐16 metal organic frameworks, manganese oxide nanotubes, and vanadium oxide nanoscrolls. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>